2016
DOI: 10.3847/2041-8205/817/2/l14
|View full text |Cite
|
Sign up to set email alerts
|

The Vla Nascent Disk and Multiplicity Survey: First Look at Resolved Candidate Disks Around Class 0 and I Protostars in the Perseus Molecular Cloud

Abstract: We present the first dust emission results toward a sample of seven protostellar disk candidates around Class 0 and I sources in the Perseus molecular cloud from the VLA Nascent Disk and Multiplicity (VANDAM) survey with ∼0 05 or 12 AU resolution. To examine the surface brightness profiles of these sources, we fit the Ka-band 8 mm dust-continuum data in the u, v-plane to a simple, parametrized model based on the Shakura-Sunyaev disk model. The candidate disks are well-fit by a model with a disk-shaped profile … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 44 publications
11
93
0
Order By: Relevance
“…This gradient suggests that the binary system is physically linked (Chen et al 2009). A study of dust continuum emission at 8 mm by Segura-Cox et al (2016) suggests a Keplerian disk with a radius 25 au. A similar study from CALYPSO observations at 1.3 mm also suggests an unresolved Keplerian disk with a radius <60 au (Maury et al 2019).…”
Section: Appendix H: Comments On Individual Sourcesmentioning
confidence: 99%
“…This gradient suggests that the binary system is physically linked (Chen et al 2009). A study of dust continuum emission at 8 mm by Segura-Cox et al (2016) suggests a Keplerian disk with a radius 25 au. A similar study from CALYPSO observations at 1.3 mm also suggests an unresolved Keplerian disk with a radius <60 au (Maury et al 2019).…”
Section: Appendix H: Comments On Individual Sourcesmentioning
confidence: 99%
“…A few studies have compared the observations of Class 0 protostars to the outcome of models, either vanalytically (see, e.g., Frau et al 2011) or from magneto-hydrodynamical simulations (see, e.g., Maury et al 2010Maury et al , 2018. These studies have shown that magnetized models of protostellar formation better reproduce the observed small-scale properties of the youngest accreting protostars, for instance the lack of fragmentation and paucity of large (100 < r disk < 500 au) rotationally supported disks (Maury et al 2010(Maury et al , 2014Enoch et al 2011;Segura-Cox et al 2016) observed in Class 0 objects.…”
Section: Introductionmentioning
confidence: 99%
“…Maury et al 2010), but recently discs with radii > 30 au have been found around both Class 0 and I objects (e.g. Lee et al 2009;Choi et al 2010;Tobin et al 2012;Yen et al 2013;Codella et al 2014;Ohashi et al 2014;Harsono et al 2014;Tobin et al 2015;Aso et al 2015; Segura-Cox et al 2016;Yen et al 2017;Aso et al 2017). One hierarchical triple system even displays the sort of disc morphology that would be expected if the wider component had recently formed via the fragmentation of a circumbinary disc .…”
Section: Introductionmentioning
confidence: 99%